PATTERN OF INVOLVEMENT IN THE VILLAGE HEAD LEGISLATIVE ELECTION 2014 - SUFIYANSYAH, SUFIYANSYAH (Politika: Jurnal Ilmu Politik, 2013)
Abstract Head of Village (headman) is one of the important village institution, as village head is a representation of power in the village. Practical politics is a tool or a means to achieve a goal in a way that is easy and precise. So that the community members who participated in the process of practical politics driven by the belief that through these activities, their needs and interests channeled or note, and to some extent can influence the actions of government in the decision-making process, but on the other hand must be set in a public participation regulations . Public participation in political campaigns involving the village head is practical politics and violating prohibitions as village head is in the legislation. The purpose of the study to identify why and how the pattern of the village chief involved in the legislative election in 2014 in the village of Sungapan, Danasari village, sub-district and village Bojongnangka. Efforts to address the problem and the purpose of the research was conducted using a qualitative approach with descriptive data analysis. The results showed, that the First: The involvement of village head Sungapan by the presence of the direct instruction of Regents to support candidates and the pressure of the sub-district, second: Village Danasari influenced by loyalty to a political party, so that with high loyalty village head finally engaged to support political campaigns of candidates promoted by the PDI Struggle Hj.Irna Setiawati, Central Java SE candidates and candidates DPRD X Haji.M Agus Sukoco, SE.MM. and Third: Village Bojongnagka by family factors, where the family is his wife who become candidates Parliament all district promoted by the National Awakening Party. The pattern of involvement of the third head of the village are equally utilize its authority to direct, encourage, and urge men or society to support and give voting rights to the candidate supported by each of the village head. It is recommended for the application of strict sanctions against the village chief who violate the prohibitions in the legislation, the Election Supervisory Committee as supervisor is given the authority to take action against the village chief directly involved in political campaigns and political participation of the community is needed to monitor and control the head of the village it self . Keywords: patterns of involvement, the village head, and the election.